Respon Hasil Tanaman Mentimun (Cucumis Sativus L.) Terhadap Pemberian Trichokompos dan NPK - Siti Syahila Rahmah; Akhmad Gazali; Tuti Heiriyani (Universitas Lambung Mangkurat, 2021)
The cucumber plant (Cucumis sativus L.) is a plant that has the advantage of being cultivated, because it can be marketed both domestically and abroad. Cucumber production is still very low, an average of 10 tonnes ha-1. In an effort to increase cucumber yields, it is necessary to have precise cultivation tecniques, the use of the right dosage fertilizers (organic and inorganic), superior varieties and spacing. Trichokompost is a form of compost organic fertilizer which contains the antagonistic fungi Trichoderma sp which can support plant growth. Meanwhile, NPK fertilizer itself is a compound fertilizer containing complete nutrients needed by plants during their growth period. This study aims to determine the effect of the interaction between trichocompost and NPK fertilizers on the highest cucumber yield and to determine the dosage of trichocompost and NPK fertilizers wihch can produce cucumber fruit. This study uses a 2-factor RAK. The first factor was the trichocompost dos with 3 treatment levls, the two factor was the NPK fertilizer dosage which consisted of 3 treatment levels, so that 9 treatment combinations were obtained. until treatment was repeated 3 times, in order to obtain 27 units. This research was conducted in February-April 2020 at the Experimental Field of the Banjarbaru Faculty of Agriculture. The study indicated that application of trichocompost and NPK fertilizers at different doses had an effect on cucumber yields (number and weight of cucumber) on a single factor. The best combination of dosage treatments for the number of cucumber fruit plants is in the T220 treatment (Trichokompos 480 grams / plant). While the best combination of dosage treatments for fruit weight was found in N1 treatment (NPK dose of 48 grams / plant).